(untitled) (Economics and region, 2025)
The article presents a comparative analysis of omnichannel strategies in apparel retail, focusing on LC Waikiki, Sinsay, and INTERTOP. It examines how integrating online and offline channels affects financial performance, customer loyalty, and operational efficiency, with managerial implications for the Ukrainian market. Omnichannel is framed as a key driver of digital transformation, enabling seamless journeys and competitive advantage. The research identifies prerequisites for adoption: digital maturity, sustained IT investment, and CRM platforms that unify customer data across touchpoints. Despite implementation costs and the lack of unified standards, the shift strengthens financial resilience and customer-centric management. The companies illustrate distinct trajectories: LC Waikiki couples an extensive store network with Click & Collect and loyalty programs; Sinsay emphasizes mobile-first design, rapid experimentation, and deep integration with Instagram and TikTok; INTERTOP focuses on localized assortment, advanced CRM scenarios, and ongoing app expansion. Beyond description, the article proposes a conceptual model of enterprise–consumer interaction showing how consolidated data flows support personalized communication, demand forecasting, and supply-chain optimization—from order orchestration and store fulfilment to reverse logistics. The model posits consumer experience as the core mechanism linking integration to sustained performance. Benchmarking indicates higher basket value, stronger retention, and lower logistics costs. Satisfaction indicators (NPS, CSAT) rise when personalization depth, delivery predictability, and frictionless returns are prioritized. The findings clarify how omnichannel adoption supports competitiveness amid digital transformation and market turbulence. Despite constraints—uneven infrastructure and budget pressures—the Ukrainian apparel retail sector shows steady progress toward international practice, especially in data governance and last-mile options. The results can guide refinement of business models with emphasis on financial sustainability and operational adaptability to shocks. Ultimately, the study argues that omnichannel retailing is not a passing fashion but a strategic necessity for long-term viability, loyalty, and disciplined, data-driven execution in the digital economy.